2001
DOI: 10.1126/science.1062374
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Nuclear NF-κB Action Regulated by Reversible Acetylation

Abstract: The nuclear expression and action of the nuclear factor kappa B (NF-kappaB) transcription factor requires signal-coupled phosphorylation and degradation of the IkappaB inhibitors, which normally bind and sequester this pleiotropically active factor in the cytoplasm. The subsequent molecular events that regulate the termination of nuclear NF-kappaB action remain poorly defined, although the activation of de novo IkappaBalpha gene expression by NF-kappaB likely plays a key role. Our studies now demonstrate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
949
4
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,137 publications
(990 citation statements)
references
References 22 publications
19
949
4
5
Order By: Relevance
“…p300/CBP is also able to increase acetylation of RelA, which prolongs NFkB-DNA binding (Chen et al, 2001). On the other hand, histone deacetylase has been reported to reduce RelA acetylation and suppressed NFkB-regulated gene expression (Chen et al, 2001). We also observed that AhR overexpression reduced histone deacetylase activity (data not shown).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…p300/CBP is also able to increase acetylation of RelA, which prolongs NFkB-DNA binding (Chen et al, 2001). On the other hand, histone deacetylase has been reported to reduce RelA acetylation and suppressed NFkB-regulated gene expression (Chen et al, 2001). We also observed that AhR overexpression reduced histone deacetylase activity (data not shown).…”
Section: Discussionmentioning
confidence: 51%
“…p300/CBP is a coactivator for AhR and NFkB and has histone acetyltransferase activity (Tian, 2009). p300/CBP is also able to increase acetylation of RelA, which prolongs NFkB-DNA binding (Chen et al, 2001). On the other hand, histone deacetylase has been reported to reduce RelA acetylation and suppressed NFkB-regulated gene expression (Chen et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in nuclear NF-kB caused by TSA was partly suppressed in the presence of the NF-kB inhibitor SN50, so TSA may affect the translocation of NF-kB. However, Chen et al 20 reported that TSA prolonged both TNF-induced DNAbinding activity and the presence of NF-kB in the nucleus, delaying the export to the cytoplasm after binding with IkB. Thus, it is more likely that TSA acetylates nuclear p65 and prolongs the retention of NF-kB in the nucleus.…”
Section: Discussionmentioning
confidence: 97%
“…NF-kB is subjected to reversible acetylation, and HDACs play important roles in its deacetylation. 19,20 Trichostatin A (TSA) is a natural HDACi that promotes histone hyperacetylation and strongly induces apoptosis by altering the expression of some apoptotic genes. [21][22][23] However, it was also reported to show relatively modest antitumor activity in cases of head and neck squamous cell carcinoma (SCC) cells.…”
Section: Introductionmentioning
confidence: 99%
“…Our laboratory has shown that the activation and repression of NF-kB-responsive genes is a dynamic process, with continual exchanges between co-activator and co-repressor complexes (Hoberg et al, , 2006. Upon the termination of transcriptional activation, much of NF-kB is removed from the nucleus and sequestered in the cytoplasm by newly synthesized IkBa, which resets the pathway for subsequent reactivation (Chen et al, 2001). This mechanism may account for the nuclear export of the NF-kB heterodimer, but it may not account for the termination of NF-kB transcription.…”
Section: Introductionmentioning
confidence: 99%